Bridges or Barriers? Conceptualization of the Role of Multiple Identity Gateway Groups in Intergroup Relations - Levy, Aharon; Saguy, Tamar; Halperin, Eran; van Zomeren, Martijn (Frontiers in Psychology, 2017)
The modern era of globalization has been accompanied by a massive growth in interconnections between groups, and has led to the sharing of multiple identities by individuals and groups. Following these developments, research has focused on the issue of multiple identities, and has shed important light on how individuals who hold these complex forms of identity feel and behave, and on the reactions they elicit from members of other groups. However, the potential of groups with such multiple identities (e.g. biracials, immigrants, etc.) to affect the intergroup relations between the groups that represent the respective sources of the different identities (e.g. Blacks and Whites, country of origin and country of residence, etc.) has not been examined to date. Accordingly, in this paper, we first systematically explore the potential of groups in which people identify with multiple social categories, or groups that are perceived as such by others, to play a role in intergroup dynamics. Next, we offer a theoretical framework outlining what functions groups of people with shared multiple identities may serve (as bridges or barriers) by proposing how their presence may facilitate or deteriorate intergroup relations. Finally, we present recent empirical research examining how groups of people with shared multiple identities can act as gateways and bridge the cleft between two separate groups that represent the respective sources of their different identities, and discuss the theoretical and practical implications for the field of intergroup relations.